Principles of Sampling in Educational Research in Higher Education - Ahrens, Andreas; Zascerinska, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Innovation and creativity in European society are fostered via a dynamic and flexible European higher education based on the integration between education and research at all levels (Communiqué, 2009). The synergy between education and research is effeciently driven via educational research. Sampling as an element of the educational research has a two-fold role: sample size is inter-connected with statistical analysis of the data and generalisation. Against this background, little attention has been given to principles of sampling in educational research. The research question is as follows: what principles form sampling in educational research? The aim of the research is to analyse scientific literature and work out principles of sampling in educational research underpinning elaboration of a new research question for further studies in educational research. The present research involves a process of analysing the meaning of the key concept “principle”. In the empirical study, explorative research was employed. Interpretive research paradigm was used. The empirical study involved six experts from different countries in February 2013 – July 2014. The findings of the research allow drawing the conclusions on the elaborated principles of sampling in educational research. Directions of further research are proposed.